ASSESSMENT OF THE MORPHOLOGICAL STATE OF TARGET ORGANS IN WISTAR RATS THAT WERE EXPOSED TO COMBINED VIBRATION AND NOISE IN A CHRONIC EXPERIMENT - Савченко, Олег Андреевич; Новикова, Ирина Игоревна; Потеряева, Елена Леонидовна; Чуенко, Наталья Федоровна (Medicine in Kuzbass, 2025)
The assessment of the morphological state of the target organs of Wistar rats exposed to combined general vibration and noise in a chronic experiment model helps to identify the initial pathological changes in the internal organs that trigger accelerated aging processes. The aim of the study is to assess the morphological condition of the target organs of Wistar rats that were subjected to combined exposure to overall vibration and noise in the model conditions of a chronic experiment. Materials and methods. The study involved 60 Wistar laboratory rats divided into 2 groups (experimental, which was under the combined influence of general vibration and noise (at the level of 1.5 MPU), and comparison group (intact animals)) There were 30 individuals (15 females and 15 males) each, in which a morphohistological analysis of the tissues of internal organs was carried out in 180-day dynamics with an interval of 2 months (after 60-120-180 days). In addition, for background analysis, five individuals of each sex were selected for the comparison group. On the 0th day (background), and after 60-120-180 days, 10 rats from each group were euthanized using chloroform (3-5-10 ml of chloroform was injected into an exicator using a syringe until the rats were in a state of narcosis) and necropsied for histopathological studies. The sections were stained with hematoxylin and eosin. Animal experiments were conducted in accordance with the European Convention for the Protection of Animals Used for Scientific Purposes, after approval by the Ethics Committee of the Novosibirsk Research Institute of Hygiene. Results and their discussion. The results of the study indicate the negative combined effect of whole-body vibration and noise (1.5 MAC) on the morphological structure of the internal organs of Wistar rats. Primary pathological changes are already detected after 60 days of the experiment, while after 180 days there is a significant intensification of structural disturbances, especially in the heart, liver, and kidneys. Conclusion. The development of structural pathological changes in two or more internal organs in rats of the experimental group (exposed to combined effects of general vibration and noise) can be considered as one of the indicators of premature aging in warm-blooded organisms when exposed to physical factors of occupational hazards for a long time.